Practical Implications in Contemporary Dental Aesthetics—Shade Selection Assessment Using Intraoral Scanners - Alice Arina Ciocan Pendefunda; Cristina Gena Dascalu; Sebastian Bahrim; Cristina Iordache; Odette Luca; Magda-Ecaterina Antohe (Dentistry Journal)
Background/Objectives: Aesthetics is a challenging aspect to restore for both dentists and dental technicians. One of the characteristics of aesthetic restoration is the shade. The purpose of the study is to assess the accuracy of the shade selection feature of intraoral scanners (CEREC Omnican, 3Shape TRIOS) in comparison with an already established method—the VITA Easyshade V spectrophotometer (VE)—and test if there is any significant difference between the three devices. Methods: To conduct this in vitro study, the VITA Classical shade guide was used. The intraoral scanners would not be able to scan the VITA Classical as it is, hence, a study model (SM) was fabricated. To be able to test the accuracy of the intraoral scanners (IOSs) in detecting the dental color, a spectrophotometer had to be included in the study, as it was shown that it is the most accurate instrument for this purpose. Therefore, for the current study, the VITA Easyshade V spectrophotometer (VITA Zahnfabrik, Bad Sackingen, Germany) was selected. Results: The accuracy of the three devices when measuring the shade of the study model was calculated as a percentage. When comparing the primary results of the VE and the results obtained by the Omnicam and TRIOS, the latter is the most accurate (26.67%), whereas the other two scored 20%. The study also revealed the limitations of the instrumental devices that were used. Conclusions: First, both the VE and IOSs obtained unexpectedly low accuracy results. Possibly, the material VC is made of influenced the final accuracy values, but in practice, on a daily basis, dental materials represent a factor that cannot really be controlled.